2015
DOI: 10.1002/jobm.201500552
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the salinity adaptation mechanism in Penicilliopsis clavariiformis AP, a rare salt tolerant fungus from mangrove

Abstract: Penicilliopsis clavariiformis AP, a rare salt tolerant fungus reported for the first time from India was identified through polyphasic taxonomy. Scanning electron microscopy showed that the fungus has unique features such as biverticillate penicilli bearing masses of oval to ellipsoidal conidia. The fungus has been characterized for salt tolerance and to understand the relevance of central carbon metabolism in salt stress adaptation. It showed optimal growth at 24 °C and able to tolerate up to 10% (w/v) NaCl. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…These are also termed compatible solutes, as they provide osmotic balance without interfering with the cell function and proper folding of the protein. It is worth mentioning that microorganisms have evolved with a variety of transporters and efflux systems to maintain osmolarity ( Kashyap et al, 2016 ; Hoffmann and Bremer, 2017 ). There are several compounds, for example, sugar molecules (sucrose and trehalose), polyols (glycerol, glucosylglycerol, arabitols, etc.…”
Section: Introductionmentioning
confidence: 99%
“…These are also termed compatible solutes, as they provide osmotic balance without interfering with the cell function and proper folding of the protein. It is worth mentioning that microorganisms have evolved with a variety of transporters and efflux systems to maintain osmolarity ( Kashyap et al, 2016 ; Hoffmann and Bremer, 2017 ). There are several compounds, for example, sugar molecules (sucrose and trehalose), polyols (glycerol, glucosylglycerol, arabitols, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Agarases are mainly found in marine microorganisms, but have also been detected in freshwater and rhizosphere microbes . Mangrove sediments harbor abundant resources of microorganisms and enzymes, and some agarases were also found in mangrove sediments by culture‐dependent and −independent methods . For further industrial production, agarases must possess the following properties: (i) high agarose‐degrading activity; (ii) high substrate affinity; and (iii) wide working temperature and pH ranges.…”
Section: Introductionmentioning
confidence: 99%
“…Here "reversibility" is defined as the ability of a trait to be reversed to the original state [39]. In previous studies, the effects of acclimation to salinity have been confirmed in a range of organisms, for example, deciphering the salinity adaptation mechanism in Penicilliopsis clavariiformis AP, a rare salt tolerant fungus from mangrove [40], effects of short-term and developmental acclimation on salinity tolerance in the copepod Eurytemora affinis [41], effects of highsalinity seawater acclimation on the levels of D-alanine in muscle and hepatopancreas tissues of the kuruma prawn, Marsupenaeus japonicas [42], gill-specific Na + /K + -ATPase activity and α-subunit mRNA expression during low-salinity acclimation of the ornate blue crab Callinectes ornatus [43]. There are also reports demonstrating the reversibility of phenotypic plasticity in manyaquatic organisms [44,45].…”
Section: Discussionmentioning
confidence: 99%